2008
DOI: 10.1186/1471-2458-8-337
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of susceptibility to smoking among Mexican origin youth residing in Houston, Texas: A cross-sectional analysis

Abstract: Background: Survey data suggest that in Texas Latino youth exhibit higher rates of susceptibility to smoking than youth from other ethnic groups. In this analysis we examined the relationship between susceptibility to smoking and well-known risk factors associated with smoking initiation among a cohort of 11 to 13 year old Mexican origin youth residing in Houston, Texas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
58
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 59 publications
(50 reference statements)
9
58
0
1
Order By: Relevance
“…Several other studies including our own have identified cognitive susceptibility(1517, 19, 21), peer influence(14, 15, 17, 25), age(16, 20, 22), and male sex(14, 17, 20, 22) as important risk factors for smoking experimentation. Positive outcome expectations(14, 15, 20, 22, 23), household smoking(1417), neighborhood characteristics(52), anxiety and depression(25, 53), and school suspensions(54)have also been shown to be associated with smoking experimentation in several studies.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Several other studies including our own have identified cognitive susceptibility(1517, 19, 21), peer influence(14, 15, 17, 25), age(16, 20, 22), and male sex(14, 17, 20, 22) as important risk factors for smoking experimentation. Positive outcome expectations(14, 15, 20, 22, 23), household smoking(1417), neighborhood characteristics(52), anxiety and depression(25, 53), and school suspensions(54)have also been shown to be associated with smoking experimentation in several studies.…”
Section: Discussionmentioning
confidence: 62%
“…Positive outcome expectations(14, 15, 20, 22, 23), household smoking(1417), neighborhood characteristics(52), anxiety and depression(25, 53), and school suspensions(54)have also been shown to be associated with smoking experimentation in several studies. Our study also found that family cohesion, co-worker smoking status, and acculturation were associated with smoking experimentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eine weitere Studie bei Jugendlichen in Ungarn zeigte keinen signifikanten Zusammenhang [41]. Zwei Studien bei Jugendlichen im Alter 11-13 Jahre untersuchten in den USA einerseits das Experimentieren mit Zigaretten [54], andererseits die Anfällig-keit für das Beginnen mit dem Rauchen [56], beide aber ohne für den "objektiven" Sozialstatus zu kontrollieren. Von den Jugendlichen, die mit Zigaretten experimentieren, befanden sich 63,6% in der Gruppe der niedrigen SSS-Stufen (dichotomisiert am Median) und 36,4% in der Gruppe der höheren SSS-Stufen (p<0,01).…”
Section: Rauchenunclassified
“…2023 These high rates are a matter of concern not just because of the implications on the parent’s health, but because parental smoking results in adverse health effects in children due to secondhand smoke exposure 17,24–27 and is a risk factor for smoking susceptibility and initiation in children. 2832 Furthermore, up to 50% of these parental smokers and their children are from low-income households, 22,33 have limited interactions with a pediatric primary care provider, and many utilize the PED for nonurgent complaints. 3436 Thus, they are unlikely to receive tobacco prevention interventions in the primary care setting.…”
mentioning
confidence: 99%